Establishment of the emergency material reserve mechanism for public health emergencies and optimization of the management of various functional departments - Sun, Yumeng (Frontiers in Public Health, 2023)
Public health emergencies refer to emergencies caused by various factors that may cause serious harm to society. This paper mainly discusses how to establish an emergency reserve mechanism for public health emergencies. This paper proposes a comprehensive evaluation system for emergency response capabilities based on analytical methods, and analyzes the emergency response to public health emergencies and various functional management departments. The experimental results show that the implementation rate of disease prevention and control projects in the city center is 59.3%, and the average completion rate of inspection projects by district and county health supervision agencies is 45.8%. However, these achievements are far from enough. Therefore, the training of relevant personnel should be strengthened and run through the material reserve work from beginning to end. At the same time, an emergency material reserve system should be established. According to actual needs, timely provide emergency disposal materials to ensure normal supply. In response to the current public health emergencies, multiple departments and units should further strengthen management personnel allocation and optimize work processes to promote the development of public health.